2014
DOI: 10.1245/s10434-014-4252-y
|View full text |Cite
|
Sign up to set email alerts
|

The 21-Gene Recurrence Score and Locoregional Recurrence in Breast Cancer Patients

Abstract: Purpose Although the 21-gene recurrence score (RS) assay has been validated to assess the risk of distant recurrence in hormone receptor-positive breast cancer patients, the relationship between RS and the risk of locoregional recurrence (LRR) remains unclear. The purpose of this study was to determine if RS is associated with LRR in breast cancer patients and whether this relationship varies based on the type of local treatment [mastectomy or breast-conserving therapy (BCT)]. Methods 163 consecutive estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Mamounas et al first reported this association in 895 tamoxifen treated patients from the NSABP B-14 and B-20 trials (p<0.001), 424 chemotherapy and tamoxifen treated patients from the B-20 trial (p=0.028), and 355 placebo patients from the B-14 trial (p=0.022)[28]. LRR was associated with RS>24 in patients treated with total mastectomy in another smaller study[29]. In contrast, a retrospective analysis of 388 patients treated with breast conservation, radiation and adjuvant systemic chemotherapy in the ECOG E2197 trial showed no association between LRR and RS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mamounas et al first reported this association in 895 tamoxifen treated patients from the NSABP B-14 and B-20 trials (p<0.001), 424 chemotherapy and tamoxifen treated patients from the B-20 trial (p=0.028), and 355 placebo patients from the B-14 trial (p=0.022)[28]. LRR was associated with RS>24 in patients treated with total mastectomy in another smaller study[29]. In contrast, a retrospective analysis of 388 patients treated with breast conservation, radiation and adjuvant systemic chemotherapy in the ECOG E2197 trial showed no association between LRR and RS.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the RS and LRR was first suggested in large patient cohorts from National Surgical Adjuvant Breast and Bowel Project (NSABP) trials B-14 and B-20[28]. However, subsequent smaller studies, including retrospective analysis of a subset of patients in the E2197 prospective randomized trial by the Eastern Cooperative Oncology Group (ECOG), did not confirm this finding[2931]. …”
Section: Introductionmentioning
confidence: 99%
“…21 Over the past decade, molecular taxonomy has revealed molecular heterogeneity of BC and has been shown to provide more accurate prognostic information. [22][23][24] But the actual role of molecular techniques in clinical practice is limited by their availability. 20 Thus, BC management relies largely on inexpensive and routine morphological assessment of H&E images coupled with biomarker semi-quantification of IHC images.…”
Section: Routine Prognostic Prediction Based On Hande Histopathology Immentioning
confidence: 99%
“…Due to the multigene panel including genes related to biological behavior such as cancer metastasis and invasion, the clinical utility of multigene panels will be expanded as studies continue. Jegadeesh et al found RS > 24 was related with LRR in patients who received mastectomy and that the 5-year LRR rate was 27.3% versus 10.7% in patients of RS ≤ 24, indicating patients with RS > 24 may benefit from post-mastectomy [ 33 ]. The recently published report from the NSABP B-28 also showed that RS was a strong predictive factor of LRR in ER-positive, node-positive breast cancer after treatment; the final result will reveal how RS helps in selecting patients for comprehensive radiology, which may broaden the clinical utility of RS [ 34 ].…”
Section: Present and Prospective For Multigene Panelsmentioning
confidence: 99%